(3TQM efgGL GdhUhd Zdi Yde GdCUhds - (3LeGd GdOjf YHO GdQMje Hf MSf GdESfhi GdTGaYjs; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s ((3YHO Gddg Hf eMeO Hf YHO Gddg GdYdeGhi s)
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg bhdg (B: (3bGd GdaU GdKGdK ai GdeNUU hgh eJUd hefaUd , aGdeJUd CQHYI (B: (3GdChd GdESJKfGA ,hgh GdENQGL HEdGZjQ GdUaI hfMhgG s
(3BNQgG (B:s
(3dCf ePGgH GdCQHYI bO EfJTQJ hYde JbjjO eWdbgG HNdGa ePgH ZjQge aQV Gddg Yfge hGQGVGge hMTQfG ai ReQJge Efg QMje hOhO Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3hbO Je GdTGQM JCdjaI SfI (B741(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs